Full Day School Management In Accelerating The Realization Of The Pancasila Student Profile And Rahmatan Lil‘Alamin Values - Dian Hikmayana; Rifqi As’adah; Shofwan Aljauhari; Sulistyorini; Ngainun Naim (International Journal of Education Management and Religion, 2026)
Full-day school management plays a strategic role in shaping students’ character based on the values of Pancasila and Rahmatan Lil‘Alamin (mercy for all creation). This study aims to describe the planning, implementation, and evaluation of full-day school management in accelerating the realization of the Pancasila Student Profile and Rahmatan Lil‘Alamin values at MI Al-Kautsar Durisawo Ponorogo and MI Ma’arif Cekok Ponorogo. This research employed a qualitative approach with a multi-case study design. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using an interactive model comprising data collection, condensation, display, and conclusion drawing. Data validity was ensured through credibility, transferability, dependability, and confirmability tests. Findings show that: (1) full-day school planning includes curriculum integration, human resource development, infrastructure improvement, student competence enhancement, stakeholder participation, and financial management; (2) implementation involves integrating the national and religious curricula, improving teacher competencies through professional development, organizing student activities, and engaging communities in parenting and social programmes; and (3) evaluation is conducted through curriculum review, teacher assessment, infrastructure monitoring, student development evaluation, and financial transparency. The study concludes that effective full-day school management significantly accelerates the realization of students with Pancasila character and Rahmatan Lil‘Alamin identity   producing graduates who are faithful, knowledgeable, ethical, and contribute positively to universal humanity.